Effects Study of Some Common Food Additives on Gene Expression of TPO Gene in Young Male Rats - Sarmad A. Abbas, Hussein A. Al-Hamadawi (Pakistan Journal of Medical & Health Sciences, 2022)
This study was conducted in an animal house / Department of biology / Al-Qadisiyah University from November 2021 to February 2022, To study the effect of food additives on gene expression Thyroid Peroxidase (TPO) for the thyroid gland This study included 32 young male rats, It was randomly divided into four equal groups, The control group, which dosed 1 ml of normal drinking water for the duration of the experiment and for a period of 30 days, The first treatment group (T1) dosed tetrazine dye at a concentration of 25 mg / kg of body weight for 30 days, The second treatment group (T2) was dosed with chocolate brown dye HT at a concentration of 200 mg / kg of body weight during the 30-day trial period, The third treatment group (T3), which was dosed with the preservative sodium benzoate at a concentration of 25 mg / kg of body weight during the 30-day trial period. The results of the statistical analysis of the molecular study of the gene expression of the enzyme thyroid peroxidase(TPO) No significant change (p >0.05) In the first group (T1) , second group (T2) And the third group (T3) when compared to the control group. And there was a significant increase (p<0.05) in the third group (T3) compared to the first group (T1) and the second (T2). On the other hand, the results of the immunohistochemistry study of the immune reaction showed the presence of TPO enzyme in the cytoplasm and tops of the follicular cells of the thyroid gland in the control group, and the intensity of (TPO) immunostaining was high in the mentioned sites. s for the first treatment group (T1) and the second treatment group (T2), the immune reaction was weak, meaning that the (TPO) enzyme was absent its gene expression disappeared or decreased in the cytoplasm and the tops of the membranes of the vesicular cells of the thyroid gland. The results of the third treatment group (T3) also indicated that it retained the dye because the strength of the immunostaining of the enzyme (TPO) was clear, but with a lower intensity than the control group. (TPO) gene expression was present in the cytoplasm and tops of the follicular cells of this group, but less than that of the control group. We conclude that the additives have negative effects on the expression of the enzyme (TPO) enzyme, as they lead to a defect in the function of the thyroid gland and should be minimized, especially in children's food containing it. Keyword: thyroid gland, immunnohistochemical ,tartrazine , benzoatsodium, chocolatebrown HT E 155, expression of TPO